Pengaruh Kepribadian, Demografi dan Lingkungan Terhadap Minat Berwirausaha Penjual Martabak Manis di Kayu Agung Kabupaten Ogan Komering Ilir (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2022)
This study uses the independent variable personality (X1), demographic (X2) and environment (X3), as well as the dependent variable interest in entrepreneurship. (Y). Sources of data in the form of questionnaires obtained by survey and interview methods. From the results of the multiple regression test, it is known that personality has a significant positive effect of 0.593 on the entrepreneurial interest of selling sweet martabak in Kayu Agung, Ogan Komering Ilir Regency, demographics has a significant positive effect of 0.445 on the entrepreneurial interest of sweet martabak sellers in Kayu Agung, Ogan Komering Ilir Regency, Environment has a positive effect significant 0.395 on the entrepreneurial interest of sweet martabak sellers in Kayu Agung, Ogan Komering Ilir Regency. The results of the coefficient of determination of personality, demographic and environmental variables were able to explain the variation of entrepreneurial interest in sweet martabak sellers in Kayu Agung, Ogan Komering Ilir Regency by 60.8% while the remaining 39.2% was explained by other variables outside of this study.